Role of Olympic Reserve colleges in the training of highly qualified athletes - Karimov, A. Q. (European Journal of Research and Reflection in Educational Sciences, 2020)
The training of highly skilled athletes is one of the most significantissues today.This article discusses ideas for further improvement of specialized sports education institutions, including colleges of the Olympic reserve and the training of skilled athletes on their basis. Methodological, material, scientific, organizational aspects of training and supporting talented athletes were also studied.The methodological, material, scientific, organizational aspects of training and support of talented athletes were also studied.Keywords: Colleges of Olympic reserve, integrated system of physical education and sports system dynamics, sports reserve, biological age.